Palms are unique: clade‐level pattern of the leaf-height-seed strategy scheme - Li, Xiaolan; Fu, Shijia; Zhang, Mingming; Yu, Fei; Wang, Yang; Yi, Xianfeng (Frontiers in Plant Science, 2024)
The leaf-height-seed (LHS) plant ecology strategy scheme posits that functional traits such as leaf size, stem height and seed mass play a key role in life history of plants.Although many studies have explored the LHS scheme across plant species, to our knowledge, no study has so far linked functional trait patterns across different plant clades. Here, we first explored the LHS scheme of several plant clades, i.e., palms, other monocots, dicots and gymnosperms, to understand how potential forces drive variation of plant functional traits. We showed that phylogeny constrains plant functional traits and appears to be the most decisive factor that controls variation in seed mass irrespective of plant clades. Apart from phylogeny, a majority of variation in seed mass was explained by leaf size in palms clade, whereas by plant height in other monocots and dicots. Neither leaf size nor plant height well explained variation in seed mass of gymnosperms clade. Our study strongly suggests that different plant clades exhibit distinct LHS schemes, paving a new avenue for better understanding evolution and correlation between functional traits across sets of plant species.